The MOSDEF-LRIS survey: connection between galactic-scale outflows and the properties of z ∼ 2 star-forming galaxies. Issue 1 (30th June 2022) - Weldon, Andrew; Reddy, Naveen A; Topping, Michael W; Shapley, Alice E; Sanders, Ryan L; Du, Xinnan; Price, Sedona H; Kriek, Mariska; Coil, Alison L; Siana, Brian; Mobasher, Bahram; Fetherolf, Tara; et al.
ABSTRACT: We investigate the conditions that facilitate galactic-scale outflows using a sample of 155 typical star-forming galaxies at z ∼ 2 drawn from the MOSFIRE Deep Evolution Field (MOSDEF) survey. The sample includes deep rest-frame UV spectroscopy from the Keck Low-Resolution Imaging Spectrometer (LRIS), which provides spectral coverage of several low-ionization interstellar (LIS) metal absorption lines and Lyα emission. Outflow velocities are calculated from the centroids of the LIS absorption and/or Lyα emission, as well as the highest velocity component of the outflow from the blue wings of the LIS absorption lines. Outflow velocities are found to be marginally correlated or independent of galaxy properties, such as star-formation rate (SFR) and star-formation rate surface density (ΣSFR ). Outflow velocity scales with SFR as a power-law with index 0.24, which suggests that the outflows may be primarily driven by mechanical energy generated by supernovae explosions, as opposed to radiation pressure acting on dusty material. On the other hand, outflow velocity and ΣSFR are not significantly correlated, which may be due to the limited dynamic range of ΣSFR probed by our sample. The relationship between outflow velocity and ΣSFR normalized by stellar mass (ΣsSFR ), as a proxy for gravitational potential, suggests that strong outflows (e.g. > 200 km s −1 ) become common above a threshold of log(ΣsSFR /yr^-1 kpc^-2 ) ∼ −11.3, and that above this threshold, outflow velocity uncouples from ΣsSFR . These results highlight the need for higher resolution spectroscopic data and spatially resolved imaging to test the driving mechanisms of outflows predicted by theory.